Octamer binding proteins confer transcriptional activity in early mouse embryogenesis. - Schöler, H R (1989)
Oct4 and Oct5 are two mouse maternally expressed proteins binding to the octamer motif. Both are found in unfertilized oocytes and embryonic stem cells, whereas Oct4 is also found in primordial germ cells. In this study, the activity of the octamer motif was analysed in two embryonic stem cell lines containing Oct4 and Oct5, the teratocarcinoma-derived cell line F9 and the blastocyst-derived cell line D3. It is known that oligomerization of the octamer motif creates a powerful B-cell specific enhancer. As shown here, this oligomerized transcriptional element is also a very strong enhancer in F9 and D3 embryonic stem cells. After differentiation of the stem cells, both enhancer activity and the amount of the octamer binding proteins decrease. An intact octamer stimulates heterologous promoters in embryonic stem cells, whereas mutations in the octamer motif abolish transcriptional stimulation and binding of the octamer factors. The use of transgenic embryos demonstrates transcriptional activation in the inner cell mass but not in the trophoblast of blastocysts. The results indicate that Oct4 and Oct5 are active early in mouse development.